2002
DOI: 10.1055/s-2002-33091
|View full text |Cite
|
Sign up to set email alerts
|

Initial Reperfusion with Magnesium after Cardioplegic Arrest Attenuates Myocardial Reperfusion Injury*

Abstract: The combination of HTK cardioplegia with 15 min initial Mg(2+) (5 and 10 mM, but not 20 mM) reperfusion was clearly superior to HTK followed by immediate Krebs-Henseleit reperfusion as well as STH cardioplegia with or without initial Mg(2+) reperfusion. The high Mg(2+) concentrations in the STH solution might mask beneficial effects of Mg(2+) reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In vitro studies showed a decrease in lethal cellular injury, but in vivo studies in rabbits showed no myocardial improvement in clinically appropriate dosages (173). Magnesium ion (Mg 2+ ) is an antagonist to Ca 2+ , a cofactor to more than 300 enzymes, and when added to cardioplegia solutions myocardial recovery is enhanced (174). This effect is believed to transpire via the Ca 2+ channel blocking mechanism derived from Mg 2+ (174)(175)(176).…”
Section: Inhibition Of Myocyte Hypercontracturementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies showed a decrease in lethal cellular injury, but in vivo studies in rabbits showed no myocardial improvement in clinically appropriate dosages (173). Magnesium ion (Mg 2+ ) is an antagonist to Ca 2+ , a cofactor to more than 300 enzymes, and when added to cardioplegia solutions myocardial recovery is enhanced (174). This effect is believed to transpire via the Ca 2+ channel blocking mechanism derived from Mg 2+ (174)(175)(176).…”
Section: Inhibition Of Myocyte Hypercontracturementioning
confidence: 99%
“…Magnesium ion (Mg 2+ ) is an antagonist to Ca 2+ , a cofactor to more than 300 enzymes, and when added to cardioplegia solutions myocardial recovery is enhanced (174). This effect is believed to transpire via the Ca 2+ channel blocking mechanism derived from Mg 2+ (174)(175)(176). Mg 2+ effects on Ca 2+ are believed to also decrease MPT incidence and mitochondria injury (79).…”
Section: Inhibition Of Myocyte Hypercontracturementioning
confidence: 99%
“…A number of cardiovascular disorders have been associated with low extracellular or intracellular concentrations of Mg, including myocardial infarction, arrhythmias and congestive heart failure 1–4 . Elevated extracellular Mg concentrations are used in cardioplegic solutions, where Mg improves myocardial recovery 5,6 . Given the variety of clinical uses of elevated Mg concentrations and the implication of imbalances in Mg in cardiovascular pathophysiologies, 7–9 the clinical application of Mg therapy remains controversial in acute myocardial infarction 7,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium is an important cofactor for many enzymatic reactions 16 and could stimulate purine nucleoside formation in the intact myocardium 5,16,17 . Adenosine is known to confer significant protection to the myocardium 18–20 .…”
Section: Introductionmentioning
confidence: 99%